Exploring the recognition pathway at the human A2A adenosine receptor of the endogenous agonist adenosine using supervised molecular dynamics simulations1. Issue 6 (10th June 2015) - Sabbadin, Davide; Ciancetta, Antonella; Deganutti, Giuseppe; Cuzzolin, Alberto; Moro, Stefano
<x xml:space="preserve">Abstract</x> The putative adenosine-hA2A AR recognition pathway is suggested by a series of Supervised Molecular Dynamics (SuMD) simulations.